Pengaruh Brand Image, Life Style dan Word Of Mouth terhadap Keputusan Pembelian - Pramaseni, Cok Istri Ema Anjalika (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
The growth of donuts &coffee is currently increasingly rapid followed by a level of intense corporate competition. The contrive of this exploration problem is how to influence brand image, lifestyle, and word of mouth partially and simultaneously on purchasing selection at the Donuts & Coffee J.CO in Denpasar City with the aim to analyze the influence of brand image, lifestyle, and word of mouth on purchasing selection at J.CO Donuts & Coffee in Denpasar. The sample number of 100 respondents. Research data is collected through documentation, library studies, interviews, observations, and questionnaire dissemination. Using quantitative and qualitative analysis. With multiple linear regression analysis in which there is a F-test and t-test. Statement that solves the problem reveal that segmental and simultaneous brand image, lifestyle, and word of mouth influence on purchasing decisions at the Donuts & Coffee J.CO in Denpasar City.